A rare case of squamous cell carcinoma arising in mature cystic teratoma - Hee Kang Kyeong; Hye Rim Ku; Chang-Woon Kim; Eun Jin Heo (Korean Society of Obstetrics and Gynecology, 2018)
Mature cystic teratoma (MCT) is the most common ovarian tumor. Secondary malignant tumors rarely arise in MCTs, and squamous cell carcinoma (SCC) is the most common form of such tumors. MCT-derived SCC in situ (CIS) is mostly found together with invasive SCC; it is seldom detected alone. A 44-year-old woman with breast cancer was found to have a left ovarian cyst (size >8 cm) before treatment. She underwent bilateral salpingo-oophorectomy, and frozen biopsy showed MCT with focal proliferation of squamous epithelium and mild atypism. However, definitive pathologic diagnosis confirmed CIS arising in MCT. In addition, germline BRCA 1/2 test and human papillomavirus test of tumor tissue yielded negative results. This report is the first case of its kind in Korea. Our report can aid in clinical decision making and serve as a basis for follow-up studies on this rare type of CIS arising in MCT.